A fight for the soul of local government in rural areas: a case study of the Dalindyebo area in the Eastern Cape, 1995-2001 - Ndletyana, Mcebisi (My University, 2004)
This study documents and analyses the process of rural democratization. Specifically, it offers an insight into the experience and attitude of rural people towards democratization; the response of chiefs towards the process: and into why the government initiated the process and the strategies it employed to elicit popular consent and compliance from the rural folk and traditional leaders. The study primarily covered the period from 1995 to 2001 using the village of Xhwili, near Umtata in the Eastern Cape Province, as a case study. The study itself was a response to the polarized public debate that erupted at the onset of the democratic process. One view opposed rural democratization reasoning that rural communities were traditional therefore unsuitable for modern institutions of governance and practices. Another view contended that, on the contrary, traditional people regarded chieftaincy as illegitimate and would welcome their replacement by elected councilors and municipalities. Straddling between the opposing viewpoints was· another contention that urged for a combination of both traditional and modern institutions in local government as each had a crucial role to fulfill. Alienating either institution, it was reasoned, would either be unconstitutional or incite political instability in rural communities. Presented in this study, therefore, is an insight into how rural democratization has unfolded and addressed the concerns and anxieties that greeted its introduction in 199
A dissertation submitted in fulfillment of the requirements of the Degree of Doctor of Philosophy in Political Studies by Research to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2004
Keywords: Local Government - Eastern Cape - South Africa; Dalindyebo Area - Eastern Cape - South Africa; Eastern Cape - 1995-2001 - South Africa; Xhwili - Eastern Cape - South Africa; Rural democratization - South Africa